Soleil et ombre. - Ndi, Bill F. (Langaa RPCIG, 2010)
In this collection, Bill F. NDI resorts to more sagacious versification (rhyme constraints, alliterations and at times the alexandrine) in which appear marked influences of many a French poet. Some of his more audacious poems bring to mind Calligrams and typography of Appolinaire and Paul ... luard respectively.